The The Impact of Statute of Limitations on Efforts to Recover Corruption Assets and Public Perceptions of Justice - anastasia anastasia; Sulistyanta Sulistyanta (International Journal of Law, 2026)
Corruption eradication efforts in Indonesia not only focus on punishing offenders but also on restoring state financial losses through asset recovery. However, these efforts face numerous challenges, one of which is the existence of a statute of limitations under the Indonesian Criminal Code (KUHP), which also applies to corruption offenses. As an extraordinary crime that is often uncovered only years after its commission, the application of a statute of limitations creates a potential legal loophole that undermines the objectives of law enforcement itself. This study aims to analyze the juridical and sociological impacts of the statute of limitations in two crucial aspects: the effectiveness of corruption asset recovery and public perceptions of justice. This research employs a socio-legal methodology with a qualitative approach. Primary data were obtained from in-depth normative materials, including academic literature and insights from anti-corruption practitioners. Secondary data were collected from statutory and regulatory analysis, court decisions, scientific journals, and media reports related to corruption cases discontinued due to the statute of limitations. Data were analyzed descriptively and analytically to map the correlation between the statute of limitations, asset recovery failures, and public responses. The findings indicate that the statute of limitations significantly impedes asset recovery efforts, particularly in complex corruption cases involving money laundering and offshore asset concealment, which require lengthy investigative processes. The statutory time limit provides a semblance of legal certainty for perpetrators while hindering the state’s ability to pursue diverted assets. From a sociological perspective, the discontinuation of corruption cases due to the statute of limitations erodes public trust in the judicial system. The public perceives such outcomes as forms of impunity and injustice, whereby the law fails to address crimes that inflict substantial harm on public interests. This study recommends a review or even abolition of the statute of limitations for corruption offenses as a strategic measure to strengthen the anti-corruption regime, maximize state asset recovery, and restore societal perceptions of justice